Strategies for the identification and dissemination of the documentary heritage of the city of Ibagué. - Carrillo Orjuela, Joaquin Eduardo
This article focuses on the formulation of strategies in the area of document management focused not only on the preservation of documents, but also on the appropriation of knowledge of the contents implicit in them, by citizens through the efficient and dynamic dissemination of the documentary heritage of the city of Ibagué. The above, in the search to generate a sense of identity and relevance that contributes to the awareness of our society of the importance of preserving our memory in order not to repeat the mistakes of the past and make better decisions for the future. The main objective of the marketing strategies stems from the opportunity to value, protect, recover and actively disseminate the documentary heritage, as history and cultural identity of the Ibaguereños, through the municipal archive of Ibagué as a point of national interest. For the formulation of strategies it was necessary, in the first place, to identify and diagnose the most emblematic archives for citizen consultation and research, followed by an evaluation of the existing archives in the territorial entities of the city of Ibagué, in order to generate strategies aimed at the preservation and dissemination of such contents with a high degree of importance for the city of Ibagué. In this context, the research results propose strategies aimed at improving the Documentary Management processes focused not only on the preservation of documents, but also on the appropriation of the knowledge contained in them, by the citizens through the efficient and dynamic dissemination of the documentary heritage of the city of Ibagué. The above, in the search to generate a sense of identity and relevance that contributes to the awareness of our society of the importance of preserving our memory to avoid repeating the mistakes of the past and make better decisions for the future.